Uji Kualitas Website Admin Travel Booking Menggunakan Halstead’s Metric dan Equivalence Partitioning - Fauziah Nur Syifa; Trisana Nurul Anzali Nabil; Derrel Hendi Arifin; Rangga Sidik (Departemen Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2025)
Tripease is a travel booking admin website designed to enable admins with management roles for train tickets, hotel tickets, and user data. Blackbox testing ensures the software meets the set requirements and specifications and detects functional and performance errors. Whitebox testing is done to check the software's logical path by examining the software's logical structure and detecting errors, such as logical errors and script understanding errors. This research discusses testing the travel booking admin website using two methods: Halstead's Metric and Equivalence Partitions. This research aims to determine the success rate of features and predict the appearance of bugs on the website. White box testing with Halstead's Metric shows that the add train feature has the highest prediction of bugs (45.7%), while the add user feature is the lowest (13.4%). The average prediction of the occurrence of bugs in all features is 25.59%. Black box testing with Equivalence Partitions shows that the add user and edit user features have a low success rate because they do not succeed in the input validity test item. The add train and login features have a 100% success rate. Based on the test results, it is recommended that the code be refactored and the input validity of each feature improved.